(untitled) (The Pakistan Development Review, 1970)
Most of the writings on the benefits of agricultural mechanization begin with an analysis of the savings in cost which will be achieved if mechanical rather than animal power is used for certain agricultural operations. There have been some studies, mostly in India1, which have tried to measure these savings. The mechanization issue cannot, however, be judged solely on this criterion. In addition to bullock displacement, mechanization is likely to involve farm-labour displacement. As we have argued in a recent paper [2], the extent of such labour displacement and its social costs are among the basic issues which should be considered before going from bullocks to tractors. But leaving aside these other issues, before one can measure the cost advantage of mechanical power over animal power, one must define what the costs are and how they should be measured. For mechanical power, such measurement of costs is not difficult. We know the cost of importing the tractor and its imple¬ments. We know the costs of fuel which we have to pour into the machine every time we want it to do something. The first is clearly a fixed cost and the second, after adding repairs, maintenance, the driver’s pay, etc., is clearly a vari¬able cost.